Systematic reviews and meta-analysis - Littell, Julia H.; Corcoran, Jacqueline; Pillai, Vijayan K. (Oxford : Oxford University Press, 2008)
Highlighting the concepts necessary to understand, critique, and conduct research synthesis, this brief and highly readable introduction is an ideal resource for students and researchers alike.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social sciences -- Research -- Evaluation; Meta-analysis.